Critical Thinking and its Relationship with Levels of Emotional Intelligence of Class-Teacher Students A Field Study at Education Faculty in Tishreen University (Damascus University Journal of educational and Psychologyical sciences, 2024)
This research aimed to determine the level of critical thinking and emotional intelligence, investigate the relationship between critical thinking and levels of emotional Intelligence, and recognizing the predictive ability of emotional intelligence to critical thinking, and the research has reached (65) male and female students at first semester in (2021/ 2022), so to achieve the objectives of the current research, two tests were used: the emotional intelligence test designed by Seligman, and the Watson & Glaser critical thinking test, and the research followed descriptive methodology, and data were processed using statistical software program (SPSS), the research reached several results, the most important of which are: there is an intermediate level of critical thinking (subsidiary skills, and total score), except extrapolation skill, and emotional intelligence level was intermediate too, there is a positive strong relationship between critical thinking (subsidiary skills, and total degree) and the low and high level of emotional intelligence, and there is a predictive ability of independent variables (emotional intelligence) is found in the dependent variable (critical thinking) of the sample members.
Keywords: Critical Thinking; Emotional Intelligence; Class-Teacher Students